Ionospheric Disturbances associated with Magnetic Storms at Kodaikanal (MAUSAM, 1959)
F2 layer disturbances at Kodaikanal have been analysed for a study of the behavior of the critical frequency and the virtual height during geomagnetic storms. The disturbances have been classified for this purpose into two categories namely, the positive and negative. The chrematistics of Dst and SD variation of f0 F2 and the SD valuation of h' F at night have been discussed. The results have been explained in terms of, the quiet and disturbed day vertical drift velocities.